INTERACTION OF CROSSES AND STOCKING DENSITY ON BREEDING OF Clarias Gariepinus FROM THREE ECO-REGIONS IN NIGERIA: RIVER NIGER (N), RIVER BENUE (B) AND RIVER HADEJIA (H) - Kabir, Hassan Y.; Abubakar, Garba A.; Ikenga, Esther.E.; Mukoro, Juliana E.; Abdul-Azeez, H; Rafindadi, Halimatu .A; Galambi, Abubakar Y. (FUDMA Journal of Sciences, 2026)
This study determined the Interaction of crosses and stocking density on breeding of C. gariepinus from three eco-regions in Nigeria: River Niger (N), River Benue (B) and River hadejia (H). Interaction of cross and stocking density was significant (p<0.05) in determining the MFW of the progenies. Survival rates for progenies from the crosses irrespective of the stocking density was significantly different (p<0.05). The best survival rate (92.08%) was recorded for the cross ♀N×H♂ while the least (73.33%) was recorded for ♀H×H♂. The interaction of cross and stocking density shows that the highest mean breeding value for body depth was recorded from the cross ♀N×N♂ while the maximum breeding value for this trait at low stocking density was observed from the cross ♀H×H♂. The interaction of cross and stocking density indicates that at high stocking density, the highest mean breeding value occurred in the cross ♀B×N♂ while the maximum breeding value for this trait at low stocking density is shared between the cross ♀B×N♂ and its reciprocal ♀N×B♂. The production of fish in captivity necessitates the use of artificial means to propagate fish species. This ensures the continuous production of fish in the farm hence supply is guaranteed at any time. In captivity, fish may behave differently and gonadal development may be impaired or even cease completely. This brings the need for man to exercise some control over the reproductive process of captive fish. Induced maturation and coordinated spawning is a valuable tool for fish culturists